Próba zastosowania grzyba Beauveria bassiana (Bals.) Vuill. w ochronie lasu przed kornikiem drukarzem Ips typographus (L.) w warunkach terenowych - Grodzki, Wojciech; Kosibowicz, Mieczysław (Leśne Prace Badawcze, 2016)
In 2011–2013, trials on the use of the entomopathogenic fungus Beauveria bassiana against bark beetle ( Ips typographus ) populations were carried out under open field conditions in Norway spruce stands suffering from an outbreak in the Beskid Żywiecki Mts. in Poland. Modified pheromone traps were deployed to capture and thereafter release fungus-infected bark beetles to the forest environment. Infested spruce trees felled next to the traps remained unaffected by the transmission of the fungus to insect populations. Direct spraying or dusting of lying trap logs and suspended caged rearing bolts did not have any effect on spruce infestation by I. typographus , its reproduction success and development or natural enemies inside the bark. A very small effect on mortality rates of target as well as non-target insects overwintering in the dusted litter was observed. Treated stands, unlike control stands, were indirectly affected by the treatment, evidenced by the reduction of tree mortality due to bark beetle infestation. At present, no recommendations concerning the potential use of the fungus in forest protection can be given. However such an environmentally friendly approach represents a promising future prospect.